PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK DENGAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION PADA POKOK BAHASAN SEGIEMPAT DAN SEGITIGA - Yola Yuliendifa (Jurnal Edukasi dan Penelitian Matematika, 2020)
This study aims to develop learning tools based on a scientific approach that will be applied to the cooperative learning model of the Student Teams Achievement Division (STAD) type. The learning tools developed were RPP and LKPD for SMP class VII semester 2 on the material of squares and triangles. The quality of the RPP and LKPD developed is assessed based on aspects of validity and practicality. This development research uses the Plomp development model which consists of three stages, namely the preliminary investigation phase, the development phase (Prototyping Phase), and the assessment phase. Based on the results of the validity data analysis, it shows that the learning tools based on the scientific approach with the student teams achievement division model are very valid. Where the percentage result of the validation of the RPP is 85.22% with a very valid category and LKPD has a validity value of 81.17% with a very valid category. The Learning tool also meets the practical criteria of the questionnaire and interview results. The results of the practicality questionnaire data analysis of students were 88.09% with the very practical category. Based on these results, it can be concluded that the learning device based on the scientific approach with the Student Teams Achievement Division model on the material of squares and triangles for grade VII junior high school students can be declared valid and practical. Keywords — Development, learning devices, Scientific Approach, Student Teams Achievement Division